2005
DOI: 10.1017/s1092852900010075
|View full text |Cite
|
Sign up to set email alerts
|

Viral Vector Mediated Overexpression of Human α-Synuclein in the Nigrostriatal Dopaminergic Neurons: A New Model for Parkinson's Disease

Abstract: Parkinson's disease is predominantly a dopamine deficiency syndrome, which is produced in the brain by the loss of cells located in a small area in the ventral midbrain called the substantia nigra. Complete unilateral dopamine lesions, based on the administration of toxic substances (ie, 6-hydroxy-dopamine in rats and 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine in mice and primates) have been extremely useful in testing strategies of replacement. For example, the functional and biochemical impact of the trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 97 publications
2
15
1
Order By: Relevance
“…4L). Consistent with observations in postmortem PD brain tissue (49,50), it has been shown that the A10 neurons of the VTA are less affected by AAV-mediated α-syn overexpression than the A9 nigral neurons (51). We hypothesized that more efficient protein clearance by the ALP may confer a unique resistance to this subpopulation of DA midbrain neurons against α-syn-induced toxicity.…”
Section: -H)supporting
confidence: 74%
“…4L). Consistent with observations in postmortem PD brain tissue (49,50), it has been shown that the A10 neurons of the VTA are less affected by AAV-mediated α-syn overexpression than the A9 nigral neurons (51). We hypothesized that more efficient protein clearance by the ALP may confer a unique resistance to this subpopulation of DA midbrain neurons against α-syn-induced toxicity.…”
Section: -H)supporting
confidence: 74%
“…A53T mutant ␣-syn is reported to accelerate fibril formation compared with wild-type ␣-syn in vitro (Conway et al, 1998). In the transgenic mice, A53T mutant ␣-syn is also revealed to cause greater neurotoxicity than wild-type ␣-syn Maingay et al, 2005;Dawson et al, 2010). In our model, coexpression of A53T mutant ␣-syn and GFP developed overt degeneration of dopaminergic neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the ability to efficiently target the photoreceptor and RPE cells of the retina bilaterally suggests this technology can be used to generate primate animal models of retinal degeneration. 23 For example, a novel transgenesis approach based not on germ line transgenesis, but instead harnessing AAV vectors to overexpress causative, mutant RP genes in the photoreceptors of models such as the macaque, could offer an attractive strategy to generate primate models of retinal degeneration. 24 …”
Section: Introductionmentioning
confidence: 99%